Pengaruh Reciprocal Teaching dan Problem Based Learning terhadap Kemampuan Berpikir Kritis Peserta Didik SMA pada Materi Sistem Reproduksi - Hani Anggraeni; Sri Rahayu; Rusdi Rusdi; Ilmi Zajuli Ichsan (Biota, 2018)
Student center learning leads to changing teacher roles. This resulted in a shift in the role of teachers. Learners are required to have HOTS (High Order Thinking Skill), one of the capabilities including HOTS is critical thinking ability. The purpose of this research is to know the influence of learning model of Reciprocal Teaching (RT) and Problem Based Learning (PBL) to critical thinking ability of high school students on reproduction system material. The method used in this research is quasi experiment with Post-Test Only Control Group Design. After obtained the results of the calculation of ANOVA test one way and critical data, then obtained significance value less than 0.05 is 0.001 <0.05 then rejected H0, meaning there is a difference in the average ability of critical thinking learners. The difference of students' critical thinking ability between the RT experimental class and the Student Team Achievement Divisions (STAD) control class proves that there is an influence of the RT learning model on critical thinking skills. The involvement of learners in PBL learning can help in developing critical thinking skills, because PBL involves the ability of learners to search and investigate logically, critically and analytically so that they can formulate their own problem solving. Based on the results of research and hypothesis testing it can be concluded that there is the influence of learning Reciprocal Teaching (RT) and Problem Based Learning (PBL) on the critical thinking skills of high school students on the material reproduction system.